Characterization of the heart rate curve during a maximum incremental test on a treadmill. DOI: 10.5007/1980-0037.2011v13n4p285 - Eduardo Marcel Fernandes Nascimento; Adriano Eduardo Lima Silva; Romulo Cassio de Moraes Bertuzzi; Maria Augusta Peduti Dal Molin Kiss; Flavio Oliveira Pires (Universidade Federal de Santa Catarina, 2011)
The objective of this study was to analyze the heart rate (HR) profile plotted against incremental workloads (IWL) during a treadmill test using three mathematical models [linear, linear with 2 segments (Lin2), and sigmoidal], and to determine the best model for the identification of the HR threshold that could be used as a predictor of ventilatory thresholds (VT1 and VT2). Twenty-two men underwent a treadmill incremental test (retest group: n=12) at an initial speed of 5.5 km.h-1, with increments of 0.5 km.h-1 at 1-min intervals until exhaustion. HR and gas exchange were continuously measured and subsequently converted to 5-s and 20-s averages, respectively. The best model was chosen based on residual sum of squares and mean square error. The HR/IWL ratio was better fitted with the Lin2 model in the test and retest groups (p<0.05). The Lin2 model permitted the identification of the HR threshold (Lin2HRDP) in all subjects of the test (164 ± 16.6 bpm; 83.6% HRMAX) and retest groups (162 ± 20.0 bpm; 83.9% HRMAX). Lin2HRDP (9.2 ± 1.3 km.h-1; 67.9% speedMAX) was lower than VT2 (10.6 ± 1.5 km.h-1, 77.3% speedMAX; p<0.05), but did not differ from VT1 (8.4 ± 1.2 km.h-1, 61.6% speedMAX; p>0.05). During a treadmill incremental test, the HR/IWL ratio seems to be better fitted with a Lin2 model, which permits to determine the HR threshold that coincides with VT1.